What is Unifas and Why Should IFAS Faculty Enter Information into It? - Howard Ladewig; Glenn D. Israel (EDIS)
Unifas is a web-based information system for collecting information about a faculty members accomplishments in teaching, research, and Extension. The system is designed to help faculty provide stakeholders with a clear understanding of what faculty in the Institute of Food and Agricultural Sciences (IFAS) are achieving with the resources they receive. This document is AEC-376, one of a series of the Agricultural Education and Communication Department, UF/IFAS Extension. Original publication date April 2006.